Compressive strength assessment of high strength concrete after fire using ultrasonic test method (Research, Society and Development, 2022)
This paper aims to evaluate the non-destructive ultrasonic pulse velocity (UPV) test method for determining the compressive strength of high strength of concrete (HSC) after fire. The compressive strength was determined through destructive cylinder test and by measuring ultrasonic pulse velocity. A total of 10 equations that relate compressive strength of concrete to UPV were evaluated in a total of 20 concrete samples. None of the equations were well suited for the case of HSC. The paper proposed a new equation and the UPV test showed suitable to assessment post-fire damaged HSC.